Combining Statistical and Interpretative Analyses for Testing IT Implementation Readiness. - M, Irfan; S.J, Putra (2019)
Researchers often use interpretative data analysis to test questionnaires by confirming the results of statistical analysis, but the researchers did not elaborate comprehensively how confirmation was made. Most use statistical analysis techniques only to test and assess questionnaires. In addition, interpretive confirmation is common for experienced researchers when conducting research, in contrast to novice researchers who have problems confirming the interpretive results of the questionnaire. This study explains how to combine statistical and interpretative analysis with testing the IT implementation questionnaire on HEI. The aim is to assess the questionnaire using statistics and interpret the results of statistical analysis. This finding can help researchers to test questionnaires; confirmation results can be a consideration and knowledge to revise the questionnaire.